The Role of Traditional Markets in Improving Community Economy According To Perspective Islamic Economics - Replita, R; Effendi, Nursyirwan; Ophiyandri, Taufika; Miko, Alfan; Hardana, Ali (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Sangkumpal Bonang is a traditional market as well as an economic development creative, which is specifically characterized by Islamic economic practices. Economic system Islam is an economic system that is oriented to rahmatan lil natural. In Economics in Islam, the goal of business is not always to seek profit (material value), but it must remain so plays an important role in obtaining and providing benefits non-material benefits, both for the businessperson himself and the environment broader, such as creating an atmosphere of brotherhood and social awareness and etc. Looking at the background of the problem, a question arises, what is the role of Umbrella in improving the community's economy as well suitability in the Islamic Economic Perspective. The aim to be achieved in this research is to find out the extent of the role of the Payungi Market in improving the community's economy North Padangsidimpuan District, Metro City Center, and how Islamic economic review of market traders. Type of research the author uses field research which is descriptive in nature qualitative, the data sources used are primary and secondary data sources, while data collection techniques use interviews, observation, and documentation. Interviews were conducted with market heads, market initiators, and local people who also act as traders in the market. Observation observing the existing conditions in Payungi and around the market, and documentation used to support the data that researchers obtain in the field. The findings of this research are that the Sangkumpal Bonang Market has potential in improving the economy of the people of North Padangsidimpuan District North Padangsidimpuan City from the field of creativity and economic skills in society. Wrong the other is the business units that are being developed, such as game rides, photo spots, traditional games and others. This means that sangkumpal bonang has value more in the field of improving the economy, especially the market, it is hoped that this will be possibly become a benchmark for the emergence of markets that have more potential for improvement community economy which is of course in accordance with Islamic economics.